Community Participation In Forest Management Of Mangrove (Case Study: Mangrove Forest Area Tugurejo Semarang) - Ardiana Yuli Puspitasari; Agus Rochani; Ahmad Ali Sadikin (International Conference on Coastal and Delta Areas, 2015)
As one of the coastal ecosystem, mangrove forest is a unique and fragile ecosystem. This ecosystem has the function of ecological and economical. Mangrove forest ecological functions include: protective shoreline, prevent the intrusion of sea water, habitat, feeding ground, where the care and nursery grounds, where spawning ground for a variety of aquatic biota, and as a regulator of the micro climate. Mangrove forests which naturally grow well along the northern coast of Java is almost does not exist. Natural forest on a small scale can only be found in the conservation area.Subdistrict Tugurejo has degraded mangrove areas either by aquaculture, as well as coastal erosion. Extensive mangroves in the coastal area around the Tugurejo District of 42.20 hectares (Department of Marine Semarang, 2010). Regional Regulation of Semarang No. 7 of 2010 on Spatial Planning Green Open mention that the vast green space mangrove forested coastal areas Tugu subdistrict of 225 hectares.